Stoffgesetz zur Beschreibung des Kriech- und Relaxationsverhaltens junger normal- und hochfester Betone - Anders, Isabel (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2013)
Within this work a material law was developed which correctly describes the creep and relaxation characteristics of young and mature normal strength and high-strength concretes. It is based on an aging thermodynamically sound rheological model and considers the complex nonlinear creep behavior under constant and variable stresses. In case of relaxation the corresponding integral relation is solved by means of a numerical algorithm.